2020
DOI: 10.26599/bsa.2020.9050003
|View full text |Cite
|
Sign up to set email alerts
|

Selective peripheral neurotomy (SPN) as a treatment strategy for spasticity

Abstract: Spasticity can be caused by central nervous system dysfunction, such as cerebral palsy and stroke. The accepted pathogenesis of spasticity is that the muscles are in the state of uninhibited stretch reflex without enough control of central nervous system. So far, there is no ideal way about how to repair central nervous system. However, the uninhibited stretch reflex can be reduced, targeting the posterior root of the spinal cord and peripheral nerves innervating the limbs, which are called selective posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Spasticity can aggravate and joints may become immovable because of rigidity if timely interventions are not provided [14]. Several interventions to treat spasticity including anticonvulsant medicines, bimanual training, botulinum toxins, bisphosphonates, context-focused therapies, hip surveillance, fitness training, goal-directed training, home interventions, occupational therapies, and selective dorsal rhizotomy have been reported [15,16]. In earlier studies, we reported the assertive effects of environmental enrichment techniques and Al Fatiha administration on the behavioral and physical outcomes in spastic CP-inflicted patients [17,18].…”
Section: Ammara Rafique and Hajira Nazmentioning
confidence: 99%
“…Spasticity can aggravate and joints may become immovable because of rigidity if timely interventions are not provided [14]. Several interventions to treat spasticity including anticonvulsant medicines, bimanual training, botulinum toxins, bisphosphonates, context-focused therapies, hip surveillance, fitness training, goal-directed training, home interventions, occupational therapies, and selective dorsal rhizotomy have been reported [15,16]. In earlier studies, we reported the assertive effects of environmental enrichment techniques and Al Fatiha administration on the behavioral and physical outcomes in spastic CP-inflicted patients [17,18].…”
Section: Ammara Rafique and Hajira Nazmentioning
confidence: 99%